'Rape is a man's issue:' gender and power in the era of affirmative sexual consent. - Metz, Julia; Myers, Kristen; Wallace, Patricia (Journal of Gender Studies, 2021)
The #MeToo movement has shined light on sexual harassment and assault, creating new avenues for survivors to seek justice, outside of the justice system. People (mostly men) accused of sexual assault or harassment are publicly 'outed', and the consequence have been serious for many. #MeToo stresses that 'rape is a man's issue', arguing that men can end rape by educating themselves about gendered power, changing their behaviour, and holding other men accountable. In this contentious context, affirmative consent policies are taking root in US universities. In this paper, we ask, How does gender frame the negotiation of consent? We analyse data from our interview project on sexual consent (N = 45) to explore gendered power dynamics in subjects' reported negotiations of sexual consent. We find that participants' understandings of consent reinforced – rather than destabilized – hegemonic systems of power. Even when acting in ways that seemed consistent with feminist conceptualizations of bodily autonomy and affirmative consent, men in this study did so to protect their own interests. Affirmative consent was mediated through gender frames that stressed men's sexual entitlement. We conclude that sexual assault intervention strategies need to be reworked to address systemic, cultural, and individual-level issues.